Examining the relationships between task cohesion, self-efficacy, and competitive trait anxiety in college team sports - Aycan, A. (The Sport Journal, 2014)
The purpose of this study was to investigate the relationships between task cohesion, self-efficacy, and competitive trait anxiety in college team sports, as well as the relationship between these variables and some demographic features of the college athletes (e.g., age, gender, and sport age). The sample consisted of 230 athletes (156 males, 74 females) from 12 different college sports teams. The data were obtained using the Group Environment Questionnaire(GEQ), the Generalized Self-Efficacy Scale (GSE), and the Sport Competition Anxiety Test (SCAT). Results showed that there are significant differences between male and female groups in competitive trait anxiety and self-efficacy perceptions (p<.01). The ages of collegiate athletes and sport ages were related in a significantly negative way with perceptions of competitive trait anxiety and GI-Task. Also, these three variables have either positive or negative correlations in the study.